Characterization of urinary exosomal release of aquaporin-1 and -2 after renal ischemia-reperfusion in rats - Asvapromtada, Siree; Sonoda, Hiroko; Kinouchi, Minami; Oshikawa, Sayaka; Takahashi, Saki; Hoshino, Yuya; Sinlapadeelerdkul, Thitaporn; Yokota-Ikeda, Naoko; Matsuzaki, Toshiyuki; Ikeda, Masahiro (American journal of physiology. Renal physiology, 2018)
Acute kidney injury (AKI) is an important risk factor for the development of chronic kidney disease (CKD), and an alteration in renal water handling has been observed during the transition of AKI to CKD. Urinary exosomal release of aquaporin-1 (AQP1) and AQP2, important proteins for renal water handling, has recently been reported to predict their levels of renal expression. Therefore, we examined the patterns of urinary exosomal release of AQP1 and AQP2, and the exosomal marker proteins tumor susceptibility 101 protein (TSG101) and ALG-2 interacting protein X (Alix), in the acute and chronic phases following induction of AKI by renal bilateral ischemia/reperfusion (I/R) in rats. Blood tests and histological examinations indicated that AKI occurred before at 7 days after renal I/R ( day 7) and that renal fibrosis developed progressively thereafter. Immunoblotting demonstrated significant decreases in the urinary exosomal release of AQP1 and AQP2 during severe AKI. Urinary exosomal release of Alix and TSG101 was significantly increased on day 7. These data were also confirmed in rats with unilateral renal I/R causing more serious AKI. Urinary exosomal release of either the Ser-256- or Ser-269-phosphorylated form of AQP2, both of which are involved in apical trafficking of AQP2, was positively correlated with that of total AQP2. These results suggest that urinary exosomal release of AQP1 and AQP2 is reduced in I/R-induced AKI, whereas that of Alix and TSG101 is increased in the initial phase of renal fibrosis. Furthermore, apical trafficking of AQP2 appears to be related to urinary exosomal release of AQP2.